The Crystallization of Active Pharmaceutical Ingredients with Low Melting Points in the Presence of Liquid–Liquid Phase Separation - Wei Han Lin (MDPI AG, 2021)
Liquid–liquid phase separation (LLPS) during the crystallization of active pharmaceutical ingredients (APIs) often causes agglomeration and other quality issues in crystal products; thus, it should be avoided if possible. However, LLPS in the crystallization of APIs with low melting points cannot be circumvented in some cases due to yield considerations. The crystallization of ibuprofen in an ethanol/water mixture was studied to explore methods to reduce agglomeration in the presence of LLPS. It was found that unseeded crystallization produced agglomerates when LLPS took place. The two liquid phases resulting from LLPS underwent LLPS again when they were cooled separately, indicating the dynamic nature of LLPS. Seeding and seed ageing at a low supersaturation were very effective in mitigating agglomeration. The effects of two widely used surfactants, i.e., Tween 80 and hydroxypropyl methylcellulose (HPMC), on LLPS and crystallization were confirmed preliminarily. More work needs to be conducted to explore their usefulness in LLPS handling. The findings and techniques presented in this study may be applicable to the crystallization of other APIs with low melting points.